The study of suitability of alkaline pre-treatment for Lignin Reduction in Banana Stem and Banana Peel using response surface methodology - Anis Nabilah Ahmad (2017)
In this study, the suitability of lignin reduction in banana stem (BS) and banana peel (BP) by using alkaline pretreatment was investigated. Three parameters were tested on to reduce the lignin. The parameters are concentration of sodium hydroxide (1M, 5.5M, and 10M), contact time (1hour, 6.5 hours, 12hours) and weight of the sample (0.5g, 2.75g, 5g). The correlation coefficient for both responses was performed by using central composite design (CCD). The correlation coefficient values for banana stem and banana peel are 0.8632 and 0.1424 respectively. The optimum lignin removal condition for banana stem predicted by RSM were found at 6% with the condition of 9.76h, 7.92M and 4.98g and for banana peel at 10.09% with the condition1h, 10M and 0.5g. Alkaline pretreatment is suitable to reduce the lignin content in banana stem and banana peel. Based on the analyses done, it can be concluded that alkaline pretreatment can be used as lignin reduction in banana stem and banana peel and further research on composition on banana peel and banana stem after pretreatment for animal feeding purposes can be done.